Chat with our AI personalities
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by 4, then 8, then 12, then 16, and so on. This pattern suggests that the nth term can be represented by the formula n^2 + n, where n is the position of the term in the sequence. So, the nth term for the given sequence is n^2 + n.
Well, darling, the nth term for the sequence 18, 12, 6, 0, -6 is -6n + 24. So, if you plug in n = 1, you get 18; n = 2 gives you 12, and so on. Just a little math magic for you to enjoy!
If you mean: 6 12 18 24 then the nth term is 6n
If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
The nth term of an AP with initial term a (= u{1}) and common difference d is given by: u{n} = a + (n - 1)d In this case: a = 6 d = (12 - 6) = 6 → u{n} = 6 + (n - 1)6 But this can be simplified: u{n} = 6 + (n - 1)6 = 6 + 6n - 6 = 6n